DNA methylation and demethylation link the properties of mesenchymal stem cells: Regeneration and immunomodulation - Xin, Tian-Yi (World J Stem Cells, 2020)
Mesenchymal stem cells (MSCs) are a heterogeneous population that can be isolated from various tissues, including bone marrow, adipose tissue, umbilical cord blood, and craniofacial tissue. MSCs have attracted increasingly more attention over the years due to their regenerative capacity and function in immunomodulation. The foundation of tissue regeneration is the potential of cells to differentiate into multiple cell lineages and give rise to multiple tissue types. In addition,the immunoregulatory function of MSCs has provided insights into therapeutic treatments for immune-mediated diseases. DNA methylation and demethylation are important epigenetic mechanisms that have been shown to modulate embryonic stem cell maintenance, proliferation, differentiation and apoptosis by activating or suppressing a number of genes. In most studies, DNA hypermethylation is associated with gene suppression, while hypomethylation or demethylation is associated with gene activation. The dynamic balance of DNA methylation and demethylation is required for normal mammalian development and inhibits the onset of abnormal phenotypes. However, the exact role of DNA methylation and demethylation in MSC-based tissue regeneration and immunomodulation requires further investigation. In this review, we discuss how DNA methylation and demethylation function in multi-lineage cell differentiation and immunomodulation of MSCs based on previously published work. Furthermore, we discuss the implications of the role of DNA methylation and demethylation in MSCs for the treatment of metabolic or immune-related diseases.